Elevated alanine aminotransferase is associated with biphasic insulin secretion in the healthy elderly Han Chinese population. Issue 9 (September 2022) - Wu, Tzong-Yow; Liao, En-Chih; Chen, Yen-Lin; Lin, Yung-Feng; Liu, Shu-Hsiang; Lin, Hua-Ching; Chiu, Yi-Chou; Wu, Chung-Ze; Lin, Jiunn-Diann; Pei, Dee; Hsu, Chun-Hsien
Objective: To evaluate the relationship between alanine transaminase (ALT) level and biphasic insulin secretion (BPIS) in healthy elderly Han Chinese individuals. Methods: This cross-sectional study enrolled healthy elderly participants aged ≥60 years that were part of a health examination programme. In order to explore the correlation and severity of the clinical condition, those with any possible confounding factors known to affect insulin secretion or liver function were excluded from the study. BPIS was calculated using an equation developed previously by this research team. Results: This study enrolled 39 845 healthy elderly individuals (19 058 males and 20 787 females). Participants were stratified into four quartile groups according to their ALT level. In both males and females, the increasing ALT quartiles (ordinal variable) were associated with greater values of log-transformed first-phase insulin secretion (FPIS) and second-phase insulin secretion (SPIS). The correlation and the linear regression model showed that increasing ALT level was significantly correlated with higher log-transformed FPIS and SPIS. Conclusions: ALT was positively correlated with BPIS in a healthy elderly population in both men and women. Elevated ALT may serve as an indicating factor for developing metabolic syndrome and type 2 diabetes mellitus in healthy elderly individuals.